Ecosystem services research trends in the water tower of Asia: A bibliometric analysis from the Hindu Kush Himalaya. (February 2021) - Kandel, Pratikshya; Chettri, Nakul; Chaudhary, Sunita; Sharma, Prashanti; Uddin, Kabir
Highlights: The HKH is the water tower of Asia providing ES to half of the humanity. First review showed increasing trend with 62% papers published in last 5 years. There has been strong collaboration with 57 countries for research in the HKH. Research is skewed to eastern part mainly focusing on biophysical aspects. Holistic analysis needed considering both services and disservices at scales. Abstract: The study presents the first comprehensive overview of ecosystem services (ES) research from the Hindu Kush Himalaya (HKH), a region often referred to as the 'water tower of Asia'. Through a systematic literature search, we consolidated 439 peer-reviewed journal articles related to ecosystem services in the HKH. A bibliometric analysis was carried out to examine the temporal trend, geographical distribution, journal coverage, keywords used, authorship patterns, and collaboration networks in ES research on the region. The results showed an increasing trend in the publication of ecosystem services research on the HKH, with nearly 62 per cent of the journal articles being published in just the last five years. Most of the research has been carried out in China, followed by Nepal and India. Among the 166 scholarly journals publishing ecosystem services research on the HKH, Ecosystem Services and Sustainability are the most-used, followed by Science of the Total Environment . The keywords analysis identified a total of 1, 460 keywords used in the articles on ES. Among them, 'ecosystem services' is the most commonly used, followed by 'China', 'Nepal', conservation', and 'biodiversity.' The authorship analysis revealed that of the total of 1, 386 authors, 1, 000 co-authored ES publications. The top publishing authors are from the region; however, they are either affiliated with an international organization or based in developed countries. Research institutions from 56 countries have networked to conduct collaborative ES research in the HKH, so far. Although China has the highest number of publications, Nepal was identified as a principal collaborator with the widest country network. The existing research focuses on biophysical elements of ecosystem services, with very few published studies covering its social and political aspects and the management of ecosystem services. As the HKH is a contiguous ecosystem shared by eight countries, there is a need for regional analyses of ecosystem services. Our study concludes that ecosystem services being a multidisciplinary concept, research into it requires regional collaboration between multiple actors from varied disciplines, with a greater emphasis on social and political science, together with the biophysical sciences, for a more holistic understanding. Furthermore, it is important that ES research include the local context and issues to avoid the dominance of international perspectives and the marginalization of local concerns.